Wind-wave coupling effects on the fatigue damage of tendons for a 10 MW multi-body floating wind turbine. (1st December 2020) - Yang, Yang; Bashir, Musa; Wang, Jin; Michailides, Constantine; Loughney, Sean; Armin, Milad; Hernández, Sergio; Urbano, Joaquín; Li, Chun
Abstract: This study investigates the wind-wave coupling effects on fatigue damage of tendons that connect multiple bodies of a novel floating platform (TELWIND) supporting a 10 MW wind turbine. An aero-hydro-servo tool is developed for dynamic analysis of a multi-body floating wind turbine (FWT) platform, by incorporating AeroDyn with AQWA through a user-defined dynamic library link (DLL) to conduct simulations of the FWT subjected to wind, wave and current loadings. The comparison against FAST has validated the accuracy of the AQWA-AeroDyn coupling framework in predicting coupled responses of the FWT. A specific site in the northern coast of Scotland is selected and design load cases are examined for the estimation of the fatigue damage of the tendons of the FWT. In the absence of wind-wave coupling, the motion differences between the two bodies of the platform are larger, leading to 43.7% enhancement in the tension fluctuation of tendons in average. Consequently, the fatigue damage of the tendons is significantly overestimated. Also, the investigation on the influence of effective simulation length on the fatigue damage shows that 90% accuracy can be achieved when 20% of the simulation analysis length is decreased. Highlights: A multi-body platform developed for a 10 MW floating wind turbine is investigated. An aero-hydro-servo coupled model based on AQWA is developed and validated. Fatigue damages of the tendons are examined using coupled and decoupled methods. Neglecting the wind-wave coupling effect results in overestimations of damages. The influence of effective simulation length on the fatigue damage is investigated.